Integrating Soft Robotics with the Robot Operating System: A Hybrid Pick and Place Arm - McKenzie, Ross M.; Barraclough, Thomas W.; Stokes, Adam A. (Frontiers in Robotics and AI, 2017)
Soft robotic systems present a variety of new opportunities for solving complex problems. The use of soft robotic grippers, for example, can simplify the complexity in tasks such as the grasping of irregular and delicate objects. Adoption of soft robotics by the informatics community and industry, however, has been slow and this is, in-part, due to the amount of hardware and software that must be developed from scratch for each use of soft system components. In this paper, we detail the design, fabrication, and validation of an open-source framework that we designed to lower the barrier to entry for integrating soft robotic subsystems. This framework is built on the robot operating system (ROS), and we use it to demonstrate a modular, soft–hard hybrid system, which is capable of completing pick and place tasks. By lowering this barrier to entry through our open sourced hardware and software, we hope that system designers and Informatics researchers will find it easy to integrate soft components into their existing ROS-enabled robotic systems.